Atypical social reward anticipation as a transdiagnostic characteristic of psychopathology: A meta-analytic review and critical evaluation of current evidence. (December 2020) - Aldridge-Waddon, Luke; Vanova, Martina; Munneke, Jaap; Puzzo, Ignazio; Kumari, Veena
Abstract: Several psychopathologies (e.g. schizophrenia spectrum conditions, autism spectrum disorders) are characterised by atypical interpersonal and social behaviour, and there is increasing evidence to suggest this atypical social behaviour is related to adjusted behavioural and neural anticipation of social rewards. This review brings together social reward anticipation research in psychopathology (k = 42) and examines the extent to which atypical social reward anticipation is a transdiagnostic characteristic. Meta-analyses of anticipatory reaction times revealed that, in comparison to healthy controls, attention-deficit/hyperactivity disorder, autism spectrum disorder, and schizophrenia spectrum conditions are associated with significantly reduced behavioural anticipation of social rewards. The pooled meta-analysis of anticipatory reaction times found that the full clinical sample demonstrated significant social reward hypoanticipation in comparison to the healthy control group with a medium effect size. A narrative synthesis of meta-analytically ineligible behavioural data, self-report data, and neuroimaging studies complemented the results of the meta-analysis, but also indicated that bipolar disorder, eating disorders, and sexual addiction disorders may be associated with social reward hyperanticipation. The evaluation of existing evidence suggests that future research should better account for factors that affect reward anticipation (e.g. gender, psychotropic medication) and highlights the importance of using stimuli other than happy faces as social rewards. Highlights: Systematic review of social reward anticipation in psychopathology. Narrative synthesis of neuroimaging and self-report data. Meta-analysis of available behavioural data. Atypical social reward anticipation as a transdiagnostic characteristic.